Assistance in the Development of Anti-Bullying Media as an Effort to Internalize the Values of Religious Moderation - Ekanara, Bambang; Isfiani, Ilma Riksa; Nurbaithy, Fany; Zannah, Rofiatul (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
This scientific activity aims to provide assistance in developing anti-bullying media to elementary school teachers as an effort to internalize the values ​​of religious moderation. Assistance was provided to UPTD teachers at SD Negeri 2 Sukalila to create anti-bullying media in the form of videos and posters. The method used is Participatory Action Research (PAR). Mentoring subjects are provided with knowledge related to bullying and media development through seminar activities by expert speakers. Next, develop anti-bullying media in the form of posters and videos accompanied by the team. The results obtained were the creation of 3 posters and 3 anti-bullying videos developed by UPTD class teachers at SD Negeri 2 Sukalila which were used as anti-violence campaign media as an effort to internalize the values ​​of religious moderation. This scientific activity received a very good response from the teachers and they hope that similar activities will be carried out on an ongoing basis.